2017
DOI: 10.1080/19390211.2017.1358233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Raw Crushed Garlic (Allium sativumL.) on Components of Metabolic Syndrome

Abstract: Metabolic syndrome consists of a group of risk factors characterized by abdominal obesity, hypertension, atherogenic dyslipidemia, hyperglycemia, and prothrombotic and proinflammatory conditions. Raw garlic homogenate has been reported to reduce serum lipid levels in animal model; however, no precise studies have been performed to evaluate the effect of raw crushed garlic (Allium sativum L.) on components of metabolic syndrome. Therefore, the present study was designed to investigate the effect of raw crushed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 14 publications
2
31
1
1
Order By: Relevance
“…In a randomized placebocontrolled trial performed by Zeb F. et al, the weight loss of the subjects was demonstrated (Zeb et al, 2018). In this and other studies, administration of garlic powder caused a significant lipid-lowering effect (Higashikawa et al, 2012;Ahmad Alobaidi, 2014;Alali et al, 2017;Xu et al, 2018;Choudhary et al, 2018). Several clinical trials also confirmed hypotensive effect of garlic.…”
Section: Effectsupporting
confidence: 80%
See 1 more Smart Citation
“…In a randomized placebocontrolled trial performed by Zeb F. et al, the weight loss of the subjects was demonstrated (Zeb et al, 2018). In this and other studies, administration of garlic powder caused a significant lipid-lowering effect (Higashikawa et al, 2012;Ahmad Alobaidi, 2014;Alali et al, 2017;Xu et al, 2018;Choudhary et al, 2018). Several clinical trials also confirmed hypotensive effect of garlic.…”
Section: Effectsupporting
confidence: 80%
“…However, direct anti-atherosclerosis activity of preparations based on garlic powder was studied wider than others natural products, their ameliorating effect on the progression of cIMT was proved in randomized double-blinded placebo-controlled trials, registrated on https://clinicaltrials.gov/ (Hodis et al, 2011;Mahdavi-Roshan et al, 2013;Karagodin et al, 2016aKaragodin et al, 2016b. Garlic preparations have the most interesting and obvious cardio-protective properties since garlic is able to ameliorate the blood lipids profile by inhibiting cholesterol biosynthesis, reducing of LDL, modulate arterial hypertension, and inhibit platelet aggregation (Sobenin et al, 2008a;Sobenin et al, 2008b;Sobenin et al, 2009;Jung et al, 2014;Mahdavi-Roshan et al, 2016;Myasoedova et al, 2016;Villa et al, 2017;Choudhary et al, 2018;Sathyapalan et al, 2018;Panahi et al, 2018;Xu et al, 2018;Sedaghat et al, 2019;Adibian et al, 2019;Adab et al, 2019). In laboratory experiments, garlic extract inhibits proliferative and inflammatory cellular reactions, possesses anti-cytokine properties, has pronounced antioxidant activity, so reduces the oxidation of LDL, activates the hydralase of cholesterol esters and inhibit ACAT, so reduces the content of cholesterol esters in cells.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolic syndrome is a cluster of metabolic diseases, including abdominal obesity, hypertension, atherogenic dyslipidemia, prothrombotic, and proinflammatory conditions and the risk of this disease increases approximately five-fold and two-fold in patients affected by type 2 diabetes mellitus and cardiovascular disease, respectively [ 94 , 95 ].…”
Section: Clinical Trials On Garlicmentioning
confidence: 99%
“…In this context it is interesting to note that intake of specific foods might impact diverse physiological processes and parameters such as blood pressure and secretory processes. There are several studies which demonstrate that the consumption of garlic can lead to reduction in blood pressure which is particularly distinctive in case of hypertensive patients (Reinhart et al, 2008 ; Ried, 2016 ; Choudhary et al, 2017 ). Such processes might also impact lactation processes, e.g., with elevated milk secretion, which might directly impact suckling behavior and milk intake of the children.…”
Section: Introductionmentioning
confidence: 99%